The Historiography of Islamic Law: The Case of TÄrÄ«kh al-TashrÄ«â Literature - Maftuhin, Arif (Al-Jamiah: Journal of Islamic Studies, 2016)
TÄrÄ«kh al-TashrÄ«â (the history of sharia affairs) is a relatively new genre of Islamic historiography and very popular among students of Islamic Law. Despite its popularity, academics of Islamic historiography seem not interested in studying it. There is hardly any academic paper seriously studied the literature. This paper is a first effort to explore the TÄrÄ«khuât-tashrÄ«â literature through a historiographical analysis. As an initial exploration, it argues thatÂ TÄrÄ«kh al-TashrÄ«â is the latest development of Islamic historiography, developed in the 19th century, but it is a genre of the old Islamic historiography with some new elements. The new elements are influenced by both modern Western historiography and the need to re-open the supposedly closed gate of ijtihÄd. The paper studied books ofÂ TÄrÄ«kh al-TashrÄ«â available during the research between 2013-2015. [TÄrÄ«kh al-TashrÄ«â adalah genre yang relatif âbaruâ dalam matarantai perkembangan historiografi IslamÂ. Literatur ini sangat popular dan menjadi mata kuliah wajib di fakultas-fakultas Syariah di Indonesia maupun Timur Tengah. Hanya saja, meskipun ia sangat populer sebagai mata pelajaran,Â TÄrÄ«kh al-TashrÄ«â belum banyak menarik minat para peneliti historiografi. Makalah in berusaha mengeksplorasi literatur TÄrÄ«kh al-TashrÄ«â dengan pendekatan historiografi. Makalah ini berpendapat bahwa TÄrÄ«kh al-TashrÄ«â, meski terlihat âmodernâ dari segi kelahirannya, tidak banyak berbeda dengan literatur historiografi klasik. Perbedaan terjadi karena adanya pengaruh historiografi Barat dalam model penulisannya dan karena kebutuhan untuk membuka kembali pintu ijtihad yang tertutup. Kajian dilakukan terhadap kitab-kitab TÄrÄ«kh al-TashrÄ«â yang dapat ditemukan selama riset antara 2013-2015â]